A management instrument for team performance evaluation - Luiz Henrique da Silva; Tatiana Ghedine; Christiane Mendes Drozdek Pereira; Sônia Regina Lamego Lino; Alessandra Yula Tutida (Revista Produção e Desenvolvimento, 2021)
Purpose: This article aims to develop an instrument to assess the collective performance of work teams' production. Associated with this, this evaluation instrument is applied to two production teams from the same company in Santa Catarina, to validate it.